THE GEOMAGNETIC LATITUDE EFFECT ON THE NUCLEON AND MESON COMPONENT OF COSMIC RAYS AT SEA LEVEL - Rose, D. C.; Katzman, J. (Canadian Journal of Physics, 1956)
Measurements have been taken on the changes in intensity of the nucleon and meson components of cosmic rays during a cruise of the Canadian Naval Icebreaker Labrador into the Arctic, through the North West Passage, and circumnavigating the North American Continent. The geomagnetic latitudes covered extend from 18°N. to 89°N. The latitude knee is clearly shown at a geomagnetic latitude of about 52° in the case of the nucleon component and less definitely between 40° and 50° in the case of the meson component. The rigidity of particles arriving in a vertical direction at 52° is 2.1 Bv. and at 45° is 3.7 Bv. Meyer and Simpson have shown that changes in the primary spectrum between 1948 and 1954 probably extend up to these rigidities and such changes should, therefore, be observable at sea level. The longitude effect at low latitudes is clearly shown by differences in intensity between the measurements on the east and west sides of North America. In the case of the meson component, the magnitude of the longitude effect at these longitudes was found to be greater than that shown by Millikan and Neher in 1936. The interpretation of the meson component results above the knee is complicated by difficulties in temperature correction. In the case of the nucleon component, an apparent longitude effect exists above the knee in that there was a small difference in the intensity at high latitudes in the eastern and western parts of the North American Arctic. No satisfactory explanation is offered for this. The diurnal variation of the nucleon component at high latitudes is shown but no unusual features were found. Appreciation is expressed to the Royal Canadian Navy for making these measurements possible.